THE METHOD OF ADAPTIVE STATISTICAL CODING TAKING INTO ACCOUNT THE STRUCTURAL FEATURES OF VIDEO IMAGES - Barannik, Volodymyr; Havrylov, Dmytro; Pantas, Serhii; Tsimura, Yurii; Belikova, Tatayna; Viedienieva, Rimma; Kryshtal, Vasyl (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The paper proposes a method of improved adaptive integral arithmetic coding. This method is advisable to use in the technology of multi-level processing of video data based on the JPEG method. The technology is based on the detection of key information at several stages of video data processing. To reduce the output volume, the RLE algorithm and integral arithmetic coding are adapted to the new structure of the input data. Thus, the method of linearization of two-dimensional transformants based on zig-zag scanning was further developed. The differences of the method consist in carrying out vector intertransformation zig-zag linearization taking into account the selection of spectral components defined as complementary. The linearized decomposition approach was developed for the first time transformants based on entry into control ranges. In connection with the presence of different types of transformants in the group, the threshold is adapted according to the criterion of the total uneven number of non-equilibrium complementary components. On the basis of taking into account the probability of occurrence of dictionary elements, integrated arithmetic coding (two-dictionary integrated arithmetic coding) has been improved. Determination of current code components according to the decomposed working interval depending on the power of the dictionaries of significant elements and the number of repetitions. This allows you to additionally take into account the statistical features of the components of the RLE-structured linearized transformants and reduce the length of the arithmetic code; for the first time, a transformant compression method was created based on the reduction of various types of redundancy in groups of transformants. Comparative experimental analysis with known methods indicated that the developed technology has a higher compression ratio with reduced processing time. This makes it possible to ensure the necessary level of access and reliability in the conditions of the growth of the original volume of data.